The Order of Bourgeois Protest - Geoffey Waite (Studies in 20th & 21st Century Literature, 1986)
Relatively little theoretical work is currently being produced by Western "Leftists" on committed protest culture. Simultaneously and not by chance, Western Marxism has drifted increasingly away from solidarity with the concept and practice of the vanguard party and toward a more or less easy compact with the problematic of poststructuralism and postmodernity. This relative paucity of discussion of commitment and protest stands in significant relationship to two critical moments: first, a powerful, overtheorized tradition of Western Marxist debate about commitment and protest (Benjamin, Sartre, Barthes, Marcuse, Adorno, among others); second, a wide-spread, undertheorized work-a-day practice of "traditional" liberal (and not so liberal) academic research and pedagogy. Yet both Western Marxism and supposedly neutral scholarship in fact constitute an unacknowledged consensus: "the order of bourgeois protest." This consensus has monopolized discussion in the West of committed protest and has worked to obviate the issue of commitment to the party. The essay at hand attempts, from the perspective of Marxist-Leninism (Marx, Engels, Lenin, Gramsci, among others) to investigate and settle accounts with the order of bourgeois protest and, hence, to investigate and settle accounts with part of the prehistory of current "Leftist" sterility and impotence in the pressing matter of (cultural) politics.
Keywords: Western Leftists; protest culture; Western Marxism; Marxism; solidarity; poststructuralism; vanguard; postmodernity; Benjamin; Sartre; Barthes; Marcuse; Adorno; bourgeois protest; bourgeois; Marxist-Leninism; Marx; Engels; Lenin; Gramsci; philosophy; cultural politics; politics